An EANM position paper on the application of artificial intelligence in nuclear medicine. - Hustinx, Roland; Pruim, Jan; Lassmann, Michael; Visvikis, Dimitris (European Journal of Nuclear Medicine & Molecular Imaging, 2022)
Artificial intelligence (AI) is coming into the field of nuclear medicine, and it is likely here to stay. As a society, EANM can and must play a central role in the use of AI in nuclear medicine. In this position paper, the EANM explains the preconditions for the implementation of AI in NM and takes position.